GENETIC TRANSFORMATION AND EXPRESSION DETECTION OF TOBACCO BY USING A MULTI-GENE PLANT TRANSFORMATION VECTOR - Y. C. Ren; Y. Dong; J. Zhang; T. Qiu; M. S. Yang (Journal of Animal and Plant Sciences, 2015)
Tobacco was transformed by employing the plant transformation vector p209-Cry1Ac-Cry3A-BADH by using Agrobacterium-mediated method to obtain completely regenerated plants screened by kanamycin sulfate. PCR detection indicated out of the nine lines in which NPT II gene was detected, Cry1Ac, Cry3A, and BADH were detected in seven lines; Cry1Ac and Cry3A were detected in one line; and Cry1Ac was detected in one line. Fluorescence quantitative PCR detection indicated in all target gene lines, three target genes were differentially expressed at the transcriptional level in four lines. BADH expression was absent in three lines. ELISA analysis revealed Cry1Ac and Cry3A toxin expression were detected in all target gene lines. The content of Cry3A toxin (up to 13,749.30 ng·g-1) was significantly higher than that of Cry1Ac toxin (up to 290.70 ng·g-1). The indoor insect-resistance test showed each transgenic line with insectresistant gene inhibited the survival, growth, and development of Prodenia litura (Fabricius) larvae to varying degrees. Average corrected mortality of five lines was significantly higher than that of control, reaching up to 70.6%. Two lines were selected for further salt-tolerance research, and results showed transgenic lines had an individual salt tolerance compared with control.
Keywords: Multi-gene; plant transformation vector; tobacco; genetic transformation; expression detection